Comparison of the diagnostic quality of aspiration and core-biopsy needles for transjugular liver biopsy. Issue 12 (December 2020) - Stift, Judith; Semmler, Georg; Wöran, Katharina; Simbrunner, Benedikt; Scheiner, Bernhard; Schwabl, Philipp; Paternostro, Rafael; Pinter, Matthias; Stättermayer, Albert Friedrich; Meischl, Tobias; Beer, Andrea; Trauner, Michael; et al.
Abstract: Background: Liver biopsy remains essential for the diagnostic work-up of patients with liver disease. Aims: To evaluate aspiration vs. core-biopsy needles for transjugular liver biopsy (TJLB) in patients undergoing hepatic venous pressure gradient (HVPG) measurements. Methods: 84 patients undergoing TJLB between 06/2017 and 12/2018 were prospectively included. Liver biopsy specimens were systematically evaluated for quantitative and qualitative criteria such as number of portal tracts, sample length and fragmentation. Results: In direct comparison of paired TJLB specimens (n=35), core-biopsy samples were significantly longer (median 12 vs. 9mm, p=0.012), tended to contain more portal tracts (median 8 vs. 6, p=0.064) and were less fragmented (p<0.001), which resulted in better confidence for liver fibrosis assessment (p=0.035). However, a superior quality in terms of less fragmentation of core-biopsy specimens (p<0.05) was only confirmed in patients with HVPG ≥10mmHg or liver stiffness measurement >40kPa. In contrast, the aspiration needle provided significantly longer samples in patients with HVPG <10mmHg (median 21 vs. 12mm, p=0.007) or with liver stiffness measurement <20kPa (median 21 vs. 11mm, p=0.025). Conclusion: In patients with HVPG ≥10mmHg, we recommend to performed TJLB using core-biopsy needles, while the aspiration needle provides high quality liver biopsy specimens in patients with HVPG <10mmHg.